Analisis Kelengkapan Berkas Rekam Medis Elektronik Pada Pasien Covid-19 Di Rumah Sakit - Muhlizardy Muhlizardy; Winda Azmi Meisari (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
The medical record as a record of the patient's illness is a file that must be filled in completely. The incomplete filling of the medical record file will result in the notes contained being out of sync and difficult to identify the previous patient's health information. Therefore, the completeness of filling out the medical record file must reach 100% for 1x24 hours after the patient leaves the hospital. This study aims to determine the level of completeness of filling out electronic medical records in Covid-19 patients at PKU Muhammadiyah Gamping Hospital. The design of this research is descriptive quantitative. The sample in this study was the medical record file for Covid-19 patients in a period of one month as many as 155 medical records. The method of data collection is in the form of a checklist. The results showed that 100% of the electronic medical record files were incomplete. The most complete indicators are the results of supporting the diagnosis (100%), nursing actions (98.9), and pain assessment (93.5%).